Glow up: does a professional photoshoot intervention affect self-esteem and emotions among adolescent psychiatric patients?—A longitudinal intervention study - Winds, Kornelius; Marka, Theresa; Salcher, Bernhard; Rieser, Nicole; Skrivanek, Christine; Hochrainer, Michelle; Trost-Schrems, Julia; Rainer, Lucas J.; Hitzl, Wolfgang; Augner, Christoph; Plattner, Belinda (Frontiers in Psychiatry, 2024)
Objectives: Today online communication is shaped by a billion-dollar social media (SM) and social networking sites (SNS) industry. Visual content consumed by children and adolescents has been shown to influence behavioral patterns, state emotions and self-esteem (SE). In this study we introduced a novel intervention creating visual content through a professional photoshoot and investigated its impact on state emotions and SE in child and adolescent psychiatric (CAP) patients. Methods: Standardized and validated self-rating questionnaires were used to assess SE, state emotions, coping mechanisms, psychopathological symptoms and internet use behavior at baseline. SE and state emotions were monitored at different timepoints around a professional photoshoot within 45 CAP patients (30 female, mean age 15.1) using a longitudinal design. Results: Withinsubject repeated ANOVA and bootstrapped paired sample t-tests showed a significant fluctuation in state emotions and SE throughout the intervention. Spearman-correlations and univariate logistic regressions revealed that internalizing symptomatology and maladaptive coping significantly worsened the outcome of the intervention on state emotions and SE in girls. Internet-related variables heightened the positive effect of the intervention in boys and lowered SE in girls during the intervention. Conclusion: The photo intervention had various gender-specific effects. Boys did benefit from the intervention in terms of longitudinal outcome on positive state emotions (PE) and SE, even positively influenced by SNS and SM. Thus, it might be concluded that online social comparison was processed more beneficial in boys. In contrast, when working with visual content in girls, psychopathology and coping must be considered. Internet consumption in general, especially SM, SNS was related to low SE in girls. Nevertheless, when therapeutically accompanied, the "glow up moment" during the shoot (high on PE, SE; low on negative state emotions) could be used as an index moment for therapeutic reflection.